Prognosis of angina with and without a diagnosis: 11 year follow up in the Whitehall II prospective cohort study. Issue 7420 (16th October 2003) - Hemingway, Harry; Shipley, Martin; Britton, Annie; Page, Michael; Macfarlane, Peter; Marmot, Michael
Abstract: Objective To investigate the prognosis of angina among people with and without diagnosis by a doctor and an abnormal cardiovascular test result. Design Prospective cohort study with a median follow up of 11 years. Setting 20 civil service departments originally located in London. Participants 10 308 civil servants aged 35-55 years at baseline. Main outcome measures Recurrent reports of angina; quality of life (SF-36 physical functioning); non-fatal myocardial infarction; death from any cause (n = 344). Results 1158 (11.4%) participants developed angina, and 813 (70%) had no evidence of diagnosis by a doctor at the time of the initial report. Participants without a diagnosis had an increased risk of impaired physical functioning (age and sex adjusted odds ratio of 2.36 (95% confidence interval 1.91 to 2.90)) compared with those who had neither angina nor myocardial infarction throughout follow up. Among reported cases of angina without a diagnosis, the 15.5% with an abnormality on a study electrocardiogram had an increased risk of death (hazard ratio 2.37 (1.16 to 4.87)). These effects were similar in magnitude to those in participants with a diagnosis of angina. Conclusion Undiagnosed angina was common and had an adverse impact on prognosis comparable to that of diagnosed angina, particularly among people with electrocardiographic abnormalities. Efforts to improve prognosis among people with angina should take account of this submerged clinical iceberg.